2022
DOI: 10.1542/peds.2022-058037
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Inflammatory Bowel Disease

Abstract: Inflammatory bowel diseases (IBDs) are chronic, immune-mediated disorders that include Crohn’s disease and ulcerative colitis. A pediatric onset of disease occurs in about 10% of all cases. Clinical presentation of IBD with rectal bleeding or perianal disease warrants direct referral for endoscopic evaluation. In the absence of red-flag symptoms, a combination of patient history and blood and fecal biomarkers can help to distinguish suspected IBD from other causes of abdominal pain or diarrhea. The therapeutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 112 publications
(123 reference statements)
0
14
0
Order By: Relevance
“…Inflammatory bowel disease (IBD) is a chronic inflammatory disorder consisting of Crohn’s disease (CD), ulcerative colitis (UC), and IBD unclassified[ 1 , 2 ]. The incidence of IBD continues to rise, including pediatric-onset disease, with most recent estimates approaching 1.5-2.0 per 10000 person years in areas with the highest rates of disease (Europe, North America)[ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory bowel disease (IBD) is a chronic inflammatory disorder consisting of Crohn’s disease (CD), ulcerative colitis (UC), and IBD unclassified[ 1 , 2 ]. The incidence of IBD continues to rise, including pediatric-onset disease, with most recent estimates approaching 1.5-2.0 per 10000 person years in areas with the highest rates of disease (Europe, North America)[ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory bowel diseases (IBDs), including Crohn disease (CD) and ulcerative colitis (UC), are chronic inflammatory disorders of the gastrointestinal tract without definite etiologies. Approximately 10% of IBD cases are of pediatric onset . The incidence of pediatric-onset IBD has increased worldwide in the past 2 decades and has become a global disease burden in both high-income and low- to middle-income countries .…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 10% of IBD cases are of pediatric onset. 1 The incidence of pediatric-onset IBD has increased worldwide in the past 2 decades and has become a global disease burden in both high-income and low-to middle-income countries. [2][3][4][5] A population-based study reported that the prevalence of pediatric-onset IBD in Canada increased substantially from 33.2 per 100 000 in 2000 to 46.2 per 100 000 in 2008.…”
mentioning
confidence: 99%
“…Despite increasing numbers of biologic agents and small‐molecule drugs for UC, only two biologics, infliximab (IFX), and adalimumab, are approved by regulators for use in children in many countries, including the US Food and Drug Administration, the European Medicines Agency, and the Japanese Pharmaceuticals and Medical Devices Agency. By necessity, IFX continues to be an important option for treating moderate to severe pediatric UC 2 that is steroid‐dependent or steroid‐refractory 3 . Patients with IFX failure involving ineffectiveness or discontinuation due to adverse effects are considered likely to require colectomy, but few reports have examined factors that could decrease need for colectomy in pediatric patients with IFX failure.…”
Section: Introductionmentioning
confidence: 99%